(untitled) (Південний архів (історичні науки), 2022)
The purpose of the work. The article is devoted to the analysis of the role of the organization of cultural leisure of Kharkiv residents in the early twentieth century in the formation of the concept of urban health. The urbanization processes that led to the transformation of Kharkiv into a densely populated industrial city during the second half of the 19th century raised the issue of creating a new concept of “urban health culture”. The purpose of this article is to analyze the leisure culture of Kharkiv residents as part of the concept of “urban health” in the early twentieth century on the materials of the city press. The authors set the task to analyze how in the studied period in the urban culture of Kharkiv begins to form an idea of “healthy” leisure time, the need to spread traditions of cultural leisure among all segments of the population, involving citizens in public spaces – places of mass events. The study of the origin of the concept of “urban health” on the example of a large city in the context of rapid urbanization is also a key goal of the article. The main attention is paid to the issues of formation of urban leisure culture, creation of public spaces for organized free time of city residents, organization of mass events to educate traditions of holidays, weekends by citizens at a high cultural level. Cultural leisure was seen by local authorities and the public as countering the spread of alcoholism and other social diseases. Results and scientific novelty of the study. It is proved that urbanization processes in Kharkiv have brought to the fore the problem of developing leisure culture among Kharkiv residents as a guarantee of maintaining physical and spiritual health. Steps have been taken to expand the network of park areas, organize mass cultural events for different categories of the population, and involve Kharkiv residents in them. Kharkiv activists, in cooperation with the city authorities, promoted sports, music, dance, theater, cinema, lectures and libraries as leisure activities. Involvement of Kharkiv residents in these events depended on their social status and place of living. Unfortunately, among the poor uneducated residents of the suburbs, alcohol abuse in cheap drinking establishments remained the main form of leisure, leading to quarrels, fights, injuries and crime. Raising the educational and cultural level, expanding the network of public spaces, promoting a healthy lifestyle were determined by the leading directions of the formation of “urban health” in Kharkiv in the early twentieth century.